2017
DOI: 10.26656/fr.2017.3.023
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of Monascus-fermented durian seed for antidiabetic and antihypercholesterol agent

Abstract: In vivo evaluation of Monascus-fermented durian seed for antidiabetic and antihypercholesterol agent AbstractMonascus-fermented durian seed (MFDS) had been developed previously. This research was aimed to evaluate the MFDS for antidiabetic and antihypercholesterol agent with in vivo method using Wistar rat. The MFDS was produced by inoculating the spore suspension of Monascus sp. KJR2 into durian seed cuts and then incubated at room temperature (30°C) for 14 days. The product was dried and ground to produce MF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Additionally, the ethanol extract of durian seed fermentation products has inhibitory activity against the α-glucosidase enzyme with IC 50 of 70.7 µg/mL (Srianta et al 2013 ). Nugerahani et al ( 2017 ) reported that administration of 0.15 g of Monascus fermented durian seeds extracted with water was able to reduce glucose and cholesterol levels in the blood of Wistar rats by 12.89 and 49.30%, respectively.…”
Section: Fruit Processing By-productsmentioning
confidence: 99%
“…Additionally, the ethanol extract of durian seed fermentation products has inhibitory activity against the α-glucosidase enzyme with IC 50 of 70.7 µg/mL (Srianta et al 2013 ). Nugerahani et al ( 2017 ) reported that administration of 0.15 g of Monascus fermented durian seeds extracted with water was able to reduce glucose and cholesterol levels in the blood of Wistar rats by 12.89 and 49.30%, respectively.…”
Section: Fruit Processing By-productsmentioning
confidence: 99%
“…Waste from durian production can go as high as 70% which consists of shells and seeds (Purnomo et al 2016 ). Srianta et al ( 2012 ), Subianto et al ( 2013 ), and Nugerahani et al ( 2017 ) reported that Monascus purpureus fermentation on durian seeds is possible and has been proven to exhibit antioxidant, antihypercholesterol, and antidiabetic activities due to Monascus pigments, phenolics, and monacolin K. These compounds have different polarities, which could affect MFDS bioactivity according to the extraction solvent (Subianto et al 2013 ). This raises the potential of Monascus -fermented durian seeds (MFDS) of various forms to be sustainable and functional ingredients for food products, especially yogurts.…”
Section: Introductionmentioning
confidence: 99%
“…Monascus fermented-durian seed is a product of solid state fermentation with Monascus purpureus culture on durian seed substrate (Srianta, Novita and Kusumawati, 2012;. The MFDS potential as an anti-diabetes agent with α-glucosidase inhibition, antioxidant and in vivo anti-hyperglycemic activities (Srianta et al, 2013;Srianta et al, 2014;Nugerahani et al, 2017). MFDS has not been incorporated into food product.…”
Section: Introductionmentioning
confidence: 99%